Autonomous reconnaissance mission: development of an algorithm for collaborative multi robot communication - Ahmed, Mohiuddin; Khan, Md. Raisuddin; Billah, Md. Masum (2010)
A collaborative team of two resource constrained semi-autonomous hexapod robots have been developed that perform navigation tasks while satisfying communication constraints. Our approach is based on the use of a control structure where each hexapod performs elementary tasks, a behavior-based controller generates motion directives to achieve the collaborative tasks, and controller generates the actuator commands to follow the motion directives. The control technique has been developed for a mission where a target location spread across a static environment has to be visited once by the two hexapods while maintaining a relative given distance with wireless communication. Wireless communication under mobile ad-hoc networks are communication networks that do not rely on fixed, preinstalled communication devices like base stations or predefined communication cells. This wireless networks consist of mobile nodes which are characterized by their decentralized organization and the potentially high dynamics of the network structure, therefore ad-hoc network communication system has been the focus in this multi-robot communication. The ad-hoc network has to provide position data to support localization of the mobile robots, which might be of great importance to guide the robots to specific targets and locations. Communications standards considered for the ad-hoc network are Wireless LAN, Bluetooth and ZigBee. In this project Bluetooth and ZigBee are integrated on robots for real experiments.